Work-related risk factors for incidence of lateral epicondylitis in a large working population - Eleonore Herquelot; Alice Guéguen; Yves Roquelaure; Julie Bodin; Celine Sérazin; Catherine Ha; Annette Leclerc; Marcel Goldberg; Marie Zins; Alexis Descatha (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: This study aims to estimate the association between repeated measures of occupational risk factors and the incidence of lateral epicondylitis in a large working population. METHODS: A total of 3710 workers in a French region were included in 2002-2005, and among them 1046 had a complete follow-up in 2007-2010. At both stages, occupational health physicians assessed the presence of lateral epicondylitis and workers self-reported their occupational exposures. Poisson models were performed to assess the incidence rate ratios (IRR) separately by sex using multiple imputed data. RESULTS: The annual incidence rate of lateral epicondylitis was estimated as 1.0 [95% confidence interval (95% CI) 0.7-1.3] per 100 workers among men and 0.9 (95% CI 0.6-1.3) among women. Workers aged >45 years had higher incidence than those aged <30 years (significant at 10%). Among men, high physical exertion combined with elbow flexion/extension or extreme wrist bending (>2 hours/day) was a risk factor, with an age-adjusted IRR of 3.2 (95% CI 1.5-6.4) for workers exposed at both questionnaires [3.3 (95% CI 1.4-7.6) among women]. CONCLUSIONS: This study highlights the importance of temporal dimensions for occupational risk factors on the incidence of lateral epicondylitis. Further research should evaluate the risk associated with the duration and repetition of occupational exposure on the incidence of lateral epicondylitis.